2005
DOI: 10.1144/gsl.sp.2005.243.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and vein patterns as indicators of deformation history: a numerical study

Abstract: Fracture and vein patterns in the brittle crust of the Earth contain information on the stress and strain field during deformation. Natural examples of fracture and vein patterns can have complex geometries including combinations of extension and conjugate shear fractures. Examples are conjugate joint systems that are oriented with a small angle to the principal stress axis and veins that show an oblique opening direction. We developed a discrete numerical model within the modelling environment ‘Elle’ to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…Especially extension and strike slip deformation were accompanied by several generations of regional fractures and faults, which are cemented with calcite and minor quartz. Bedding perpendicular vein sets often follow stress oriented anastomosing patterns with regular spacing showing single extensional or conjugate extensional shear patterns [59]. These regularly spaced patterns seem to be overprinted by chaotic and very closely spaced veins that indicate the existence of high fluid pressure gradients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially extension and strike slip deformation were accompanied by several generations of regional fractures and faults, which are cemented with calcite and minor quartz. Bedding perpendicular vein sets often follow stress oriented anastomosing patterns with regular spacing showing single extensional or conjugate extensional shear patterns [59]. These regularly spaced patterns seem to be overprinted by chaotic and very closely spaced veins that indicate the existence of high fluid pressure gradients.…”
Section: Resultsmentioning
confidence: 99%
“…Natural disorder in geological media corresponds to the ubiquitous presence of Griffith's microcracks, variation in their densities and lengths and other defects, which are present at the grain scale. It has been demonstrated that fracture patterns that are observed both in the field and laboratory can be numerically reproduced by implying realistic normal distributions of breaking strength in DEM models [57][58][59][60]. The overall breaking strength of the model material, and its failure mode, is sensitive to the lower values of the quenched distribution [61][62][63].…”
Section: Methodsmentioning
confidence: 97%
“…1 The numerical scheme is built on a 2D hybrid Particle-Lattice model of unit dimension 2 that utilizes a small-scale triangular discrete spring network code inherited from the software 3 'Latte' (part of the modeling environment 'Elle', [Bons et al, 2007;Koehn et al, 2005]) as a 4 deformation isotropic porous material. The discrete lattice is then coupled with a continuum fluid 5 phase presented by a stationary square grid of equivalent or larger dimension (figure 2).…”
Section: 1) Methodologymentioning
confidence: 99%
“…Inspired by [Flekkøy et al, 2002] we extended the work of [Koehn et al, 2005] to a 3 hybrid discrete-continuum constitutive modeling approach. The scheme emphasizes the 4 evolution of rock failure in the light of underlying synergistic evolution of rock permeability 5 upon fracture growth and the consequent change in interstitial pore pressure.…”
mentioning
confidence: 99%
“…The net force F acting on a node within the network is given by (Monette and Anderson 1994;Malthe-Sørenssen et al 1998;Koehn et al 2005).…”
Section: Forces Related To Elasticitymentioning
confidence: 99%